Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1245
|View full text |Cite
|
Sign up to set email alerts
|

Hypernasality Severity Analysis in Cleft Lip and Palate Speech Using Vowel Space Area

Abstract: Vowel space area (VSA) refers to a two-dimensional area, which is bounded by lines joining F1and F2 coordinates of vowels. In the speech of individuals with cleft lip and palate (CLP), the effect of hypernasality introduces the pole-zero pairs in the speech spectrum, which will shift the formants of a target sound. As a result, vowel space in hypernasal speech gets affected. In this work, analysis of vowel space area in normal, mild and moderate-severe hypernasality groups is analyzed and compared across the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In other words, CLP datasets are usually in a low-resource scenario, which results in a poor generalization for model capacity. Secondly, previous work [16,17] have analyzed that hypernasality has obviously abnormal area in acoustic space (e.g., vowel or consonant), especially in the spectrum dimension [13]. Thus, it can be concluded that learning high quality acoustic features is beneficial for predicting hypernasality.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, CLP datasets are usually in a low-resource scenario, which results in a poor generalization for model capacity. Secondly, previous work [16,17] have analyzed that hypernasality has obviously abnormal area in acoustic space (e.g., vowel or consonant), especially in the spectrum dimension [13]. Thus, it can be concluded that learning high quality acoustic features is beneficial for predicting hypernasality.…”
Section: Introductionmentioning
confidence: 99%